Single-Particle Electron Microscopy Analysis of DNA Repair Complexes - Sawicka,M; Aramayo,R; Ayala,R; Glyde,R; Zhang,X (Methods in Enzymology, 2017)
DNA repair complexes play crucial roles in maintaining genome integrity, which is essential for the survival of an organism. The understanding of their modes of action is often obscure due to limited structural knowledge. Structural characterizations of these complexes are often challenging due to a poor protein production yield, a conformational flexibility, and a relatively high molecular mass. Single-particle electron microscopy (EM) has been successfully applied to study some of these complexes as it requires low amount of samples, is not limited by the high molecular mass of a protein or a complex, and can separate heterogeneous assemblies. Recently, near-atomic resolution structures have been obtained with EM owing to the advances in technology and image processing algorithms. In this chapter, we review the EM methodology of obtaining three-dimensional reconstructions of macromolecular complexes and provide a workflow that can be applied to DNA repair complex assemblies.